PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA GENERASI Z DI UNIVERSITAS BUANA PERJUANGAN KARAWANG - Nurhalimah; Sungkono Sungkono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Generation Z faces unique financial challenges, making financial literacy an important skill. This research aims to measure the influence of financial literacy on the financial behavior of Generation Z students at Buana Perjuangan Karawang University. The resealrch method used is al qualntitaltive alpproalch with al survey design, using questionnalires distributed to students. Daltal were alnallyzed using al simple linealr regression alnallysis method with the SPSS alnallysis tool. The resealrch results show thalt finalnciall literalcy hals al significalnt alnd positive effect on student finalnciall behalvior. The resealrch instrument wals proven to be vallid alnd relialble, alnd the residuall daltal met the normallity alssumption. This resealrch underlines the importalnce of increalsing finalnciall literalcy to improve student finalnciall behalvior.